2017
DOI: 10.3238/arztebl.2017.0255
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Intussusception After Rotavirus Vaccination

Abstract: SUMMARYBackground: In 2013, the German Standing Committee on Vaccination (Stän-dige Impfkommission, STIKO) recommended rotavirus (RV) vaccination for all infants while stating that this mildly increased the risk of intussusception, a potentially life-threatening event. Since this recommendation was issued, multiple observational studies on this topic designed as self-controlled case series (SCCS) have been published. The SCCS design is particularly suitable for the study of rare adverse effects of medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 39 publications
0
31
1
2
Order By: Relevance
“…The results from our cohort study differ somewhat from the generally increased intussusception risks reported in previous self-controlled studies 12, 30 which may be confounded by the changing within-person risk of intussusception during infanthood, and user vs. non-user cohort designs may be confounded by differences between vaccine receivers and non-receivers.…”
Section: Commentcontrasting
confidence: 99%
“…The results from our cohort study differ somewhat from the generally increased intussusception risks reported in previous self-controlled studies 12, 30 which may be confounded by the changing within-person risk of intussusception during infanthood, and user vs. non-user cohort designs may be confounded by differences between vaccine receivers and non-receivers.…”
Section: Commentcontrasting
confidence: 99%
“…Another meta-analysis of 10 SCCSs showed that RR for intussusception was 5.71 (95% CI, 4.50-7.25) from 1 to 7 days after the first dose, 1.69 (95% CI, 1.33-2.14) after the second dose, and 1.14 (95% CI, 0.75-1.74) after the third dose. 43 The SCCS evaluation is increasingly being used during the active vaccine safety surveillance, whereas an SCCS has its own limitations of measuring only the incidence of reported cases with a descriptive design rather than an analytic study. Thus, SCCSs could include potential referral bias because variation of the treatment application has no control.…”
Section: Discussionmentioning
confidence: 99%
“…Intussusception has been a concern associated with rotavirus vaccines for some time. A meta-analysis reported a significant rise in the risk of intussusception after rotavirus vaccination if the first dose was administered after three months of age [20]. India recently introduced rotavirus vaccines (Rotavac and Rotasiil), as part of the UIP, in a phased manner.…”
Section: Discussionmentioning
confidence: 99%